Synthetic Inertia Emulation And Frequency Control In Distributed PV Grid Using Battery Energy Storage System (Pokhara Engineering College Journal, 2026)
The rapid integration of distributed photovoltaic (PV) systems provides a promising solution to environmental concerns and climate obligations, yet it introduces significant challenges to power system stability. As PV penetration increases, system inertia decreases, making the grid more vulnerable to frequency deviations during contingencies such as sudden load changes, generator outages, or high PV output. Battery Energy Storage Systems (BESS) offer a viable solution by emulating synthetic inertia and providing fast frequency regulation. This study investigates the dynamic behaviour of BESS under low-inertia conditions and evaluates strategies for inertia emulation, droop-based frequency response, primary frequency response, and primary frequency regulation. An innovative approach is presented in which BESS dynamically injects or absorbs active power to mimic the inertial response of conventional synchronous generators, thereby stabilizing frequency fluctuations. The effects of BESS sizing, placement, and parameters on system performance and power losses are analyzed mathematically and through simulations. The IEEE 9-bus test system is employed to model varying PV penetration levels of 20%, 40% and 60%, along with generator outages and load scenarios. Results indicate that increasing PV penetration leads to higher Rate of Change of Frequency, deeper frequency nadir, and slower recovery. With the implementation of a 35 MVA BESS, frequency response, and steady-state frequency deviations were maintained within Nepal’s operational limits of 5% of nominal frequency. These findings demonstrate the effectiveness of BESS-based synthetic inertia in enhancing frequency stability and improving grid resilience in low-inertia, high-renewable power systems.The rapid integration of distributed photovoltaic (PV) systems provides a promising solution to environmental concerns and climate obligations, yet it introduces significant challenges to power system stability. As PV penetration increases, system inertia decreases, making the grid more vulnerable to frequency deviations during contingencies such as sudden load changes, generator outages, or high PV output. Battery Energy Storage Systems (BESS) offer a viable solution by emulating synthetic inertia and providing fast frequency regulation. This study investigates the dynamic behaviour of BESS under low-inertia conditions and evaluates strategies for inertia emulation, droop-based frequency response, primary frequency response, and primary frequency regulation. An innovative approach is presented in which BESS dynamically injects or absorbs active power to mimic the inertial response of conventional synchronous generators, thereby stabilizing frequency fluctuations. The effects of BESS sizing, placement, and parameters on system performance and power losses are analyzed mathematically and through simulations. The IEEE 9-bus test system is employed to model varying PV penetration levels of 20%, 40% and 60%, along with generator outages and load scenarios. Results indicate that increasing PV penetration leads to higher Rate of Change of Frequency, deeper frequency nadir, and slower recovery. With the implementation of a 35 MVA BESS, frequency response, and steady-state frequency deviations were maintained within Nepal’s operational limits of 5% of nominal frequency. These findings demonstrate the effectiveness of BESS-based synthetic inertia in enhancing frequency stability and improving grid resilience in low-inertia, high-renewable power systems.